Strategy and development of hydrogen energy for industrial enterprises - Bakalář, Matěj (2023)
The work solves the problem of an industrial company which, due to its photovoltaic power plant, has a surplus and shortages of electricity during the year. There are many ways to approach this issue. In this work, four model solutions were chosen, all a possibility for an industrial enterprise. The first is the sale of the surpluses to the electrical grid and to cover the shortages by buying electricity from a distributor. The second is to store the excess energy in an accumulator. The third is to convert surpluses into green hydrogen and then sell it. The fourth model stores the excess energy in hydrogen, which is then converted back into energy in times of shortages. The work evaluates the economic indicators of net present value, internal rate of return and profitability index. During the conclusion of the work, it is found that the capital investments in this thirty-year project are too high, the market and the future too uncertain, and therefore the industrial enterprise should not make any such investments in 2023, despite the attractiveness of hydrogen technologies.